Numerical Assessment on Fatigue Failure of Castellated Steel Beams under Sinusoidal Vibration - M. Jaini, Z.; Han Kit, S. K.; Feng, Y. T. (International Journal of Sustainable Construction Engineering and Technology, 2020)
Increase cost of material in the construction industry has led to the adoption of castellated steel beam as an alternative to substitute conventional steel rolled beam. However, the presence of web opening has resulted to various structural behaviour under static action and uncertainties under dynamic loading, especially fatigue failure. Therefore, this paper presents the numerical assessment on fatigue failure of castellated steel beams. The design of castellated steel beam was based on the parent steel beam of UKB 254 x 102 x 28. Meanwhile, various shapes of web opening (hexagonal, circular and rectangular) with size of 0.75D were considered. The finite-discrete element method program was used as a platform of numerical modelling. The stress range was analysed at 3 Hz of different load amplitudes of sinusoidal vibration. The fatigue life was compared among each shape of web opening at detail categories 90 and 160. At the initial load, the stress range reaches 65 MPa to 150 MPa. When the load increased, the stress range changes diminutively around 240 MPa to 280 MPa. The fatigue life attains at plateau value of 108 cycles, where circular castellated steel beams showed the best performance.